2022
DOI: 10.2147/idr.s372427
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary Role of Immunological Indicators in the Diagnosis and Prognosis of Pneumocystis Pneumonia in Non-HIV Immunocompromised Patients

Abstract: Background Pneumocystis pneumonia (PCP) has a high mortality in HIV-negative immunocompromised patients. The occurrence and development of PCP are believed to be correlated with the level of lymphocytes and their subsets. The aim of this study was to determine if the levels of lymphocyte subpopulations and immunoglobulin are associated with PCP. Methods A total of 74 immunocompromised patients were enrolled in this single-center cohort study. Diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…As shown in Fig. 2, both lymphocytic counts and proportions were significantly lower in PJP patients (0.46 × 10 9 /L, 6.8%) than in P. jirovecii-colonized patients (0.75 × 10 9 /L, 10.8%; P = 0.0004, P = 0.0009), being consistent with other studies [27]. Additionally, the percentage of B cells in lymphocytes was reduced in PJP patients (7.8% vs. 12.7%; P = 0.0187).…”
Section: Differences In Lymphocytes and Inflammatory Factors Between ...supporting
confidence: 91%
“…As shown in Fig. 2, both lymphocytic counts and proportions were significantly lower in PJP patients (0.46 × 10 9 /L, 6.8%) than in P. jirovecii-colonized patients (0.75 × 10 9 /L, 10.8%; P = 0.0004, P = 0.0009), being consistent with other studies [27]. Additionally, the percentage of B cells in lymphocytes was reduced in PJP patients (7.8% vs. 12.7%; P = 0.0187).…”
Section: Differences In Lymphocytes and Inflammatory Factors Between ...supporting
confidence: 91%
“…Adjusted data were then used to evaluate the risk of death among the 90-day survival or mortality groups using logistic regression. Explanatory variables were included in the propensity score model, including steroid burden for the underlying disease during the period of maximum AUC, days from onset to start of treatment [ 36 , 40 , 42 ], worsening respiratory status [ 30 , 40 , 43 , 44 ], lactate dehydrogenase (LDH) [ 29 , 40 ], lymphocyte count [ 35 , 42 , 45 ], and early treatment with steroids, and TMP-SMX, which had previously been implicated in increasing the risk of death. Missing values were not complemented.…”
Section: Methodsmentioning
confidence: 99%
“…In Figure 2, we have incorporated all the risk factors and grouped them by subgroups in a forest plot. Furthermore, in two retrospective studies involving non-HIV PcP patients, low CD4 lymphocyte levels appear to be associated with a worse prognosis [15,16].…”
Section: Risk Factors For Pcp In Ht Recipientsmentioning
confidence: 99%
“…Interestingly, beyond lymphocytopenia, which is one of the most studied and recognized risk factors for PcP, the role of CD4 lymphocytes in the pathogenesis of non-HIV related PcP has recently been acknowledged [15,16]. One retrospective study had demonstrated that a low level of CD4 lymphocytes is correlated with the development of PcP.…”
Section: Risk Factors For Pcp In Ht Recipientsmentioning
confidence: 99%
See 1 more Smart Citation